Digital Imaging Primer - Parkin, Alan (Springer Berlin Heidelberg : Imprint: Springer, 2016)
Digital Imaging targets everyyone with an interest in digital imaging, be they professional or private, who uses even quite modest equipment such as a PC, digital camera and scanner, a graphics editor such as Paint, and an inkjet printer. Uniquely, it is intended to fill the gap between highly technical texts for academics (with access to expensive equipment) and superficial introductions for amateurs. The four-part treatment spans theory, technology, programs and practice. Theory covers integer arithmetic, additive and subtractive color, greyscales, computational geometry, and a new presentation of discrete Fourier analysis; Technology considers bitmap file structures, scanners, digital cameras, graphic editors, and inkjet printers; Programs develops several processing tools for use in conjunction with a standard Paint graphics editor and supplementary processing tools; Practice discusses 1-bit, greyscale, 4-bit, 8-bit, and 24-bit images for the practice section. Relevant QBASIC code is supplied an accompanying CD and algorithms are listed in the appendix. Readers can attain a level of understanding and the practical insights to obtain optimal use and satisfaction from even the most basic digital-imaging equipment.